Integrated care for adults with dementia and other cognitive disorders. (2nd November 2018) - Draper, Brian; Low, Lee-Fay; Brodaty, Henry
Abstract: The importance of better care integration is emphasized in many national dementia plans. The inherent complexity of organizing care for people with dementia provides both the justification for improving care integration and the challenges to achieving it. The prevention, detection, and early diagnosis of cognitive disorders mainly resides in primary care, but how this is best integrated within the range of disorders that primary care clinicians are expected to screen is unclear. Models of integrated community dementia assessment and management have varying degrees of involvement of primary and specialist care, but share an emphasis on improving care coordination, interdisciplinary teamwork, and personalized care. Integrated care strategies in acute care are still in early development, but have been a focus of investigation in the past decade. Integrated care outreach strategies to reduce transfers from long-term residential care to acute care have been consistently effective. Integrated long-term residential care includes considerations of end-of-life care. Future directions should include strategies for training and education, early detection in anticipation of disease modifying treatments, integration of technological developments into dementia care, integration of dementia care into general health and social care, and the encouragement of a dementia-friendly society.